Amine treatment induced perovskite nanowire network in perovskite solar cells: efficient surface passivation and carrier transport. (8th January 2018) - Xiao, Ke; Cui, Can; Wang, Peng; Lin, Ping; Qiang, Yaping; Xu, Lingbo; Xie, Jiangsheng; Yang, Zhengrui; Zhu, Xiaodong; Yu, Xuegong; Yang, Deren
Abstract: In the fabrication of high efficiency organic–inorganic metal halide perovskite solar cells (PSCs), an additional interface modifier is usually applied for enhancing the interface passivation and carrier transport. In this paper, we develop an innovative method with in-situ growth of one-dimensional perovskite nanowire (1D PNW) network triggered by Lewis amine over the perovskite films. To our knowledge, this is the first time to fabricate PSCs with shape-controlled perovskite surface morphology, which improved power conversion efficiency (PCE) from 14.32% to 16.66% with negligible hysteresis. The amine molecule can passivate the trap states on the polycrystalline perovskite surface to reduce trap-state density. Meanwhile, as a fast channel, the 1D PNWs would promote carrier transport from the bulk perovskite film to the electron transport layer. The PSCs with 1D PNW modification not only exhibit excellent photovoltaic performances, but also show good stability with only 4% PCE loss within 30 days in the ambient air without encapsulation. Our results strongly suggest that in-situ grown 1D PNW network provides a feasible and effective strategy for nanostructured optoelectronic devices such as PSCs to achieve superior performances.